Bimetallic Coordination in Two-Dimensional Metal–Organic Framework Nanosheets Enables Highly Efficient Removal of Heavy Metal Lead (II) - Li, Guiliang; Liu, Yang; Shen, Yi; Fang, Qile; Liu, Fu (Frontiers in Chemical Engineering, 2021)
Two-dimensional (2D) metal-organic frameworks (MOFs) have emerged as an intriguing type of 2D materials because of its specific features of 2D morphology and designable skeleton, which has elicited great interest in environment remediation. In this work, 2D MOFs nanosheets are fabricated via a mixed-solvent solvothermal method, and a regulation strategy of metal inorganic clusters on MOF frameworks is used to construct two different 2D-MOFs with monometallic and bimetallic coordination, i. e. Ni-MOF and Ni/Cd-MOF. Binary metals coordination renders more crystal defects and vacancies in the framework, thus, compared to monometallic Ni-MOF, bimetallic Ni/Cd-MOF exhibits fewer layers (4~5 layers), higher specific surface area, larger pore size, and higher surface electronegativity, which leads to its excellent adsorption removal for Pb2+, with higher adsorption rate, affinity and superior adsorption capacity (950.61 mg/g, almost twice as high as that of monometallic Ni-MOF). Besides, the adsorption mechanism is further confirmed that the carboxyl groups (COO) from organic linker on 2D-MOFs serve as the main binding sites for Pb2+ coordination and bimetallic Ni/Cd-MOF has more active COO sites for Pb2+ capture. Thus, the bimetallic Ni/Cd-MOF regulated by heterogeneous metal atoms shows promising application for highly efficient adsorption of heavy metal ions.